Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.2174/1381612823666170609082324
|View full text |Cite
|
Sign up to set email alerts
|

Sialidases: Therapeutic and Antiatherogenic Potential

Abstract: This review focuses on the biological role and clinical relevance of relatively poor studied enzymes known as sialidases. We describe structure and function of sialic acid, in particular as a component of gangliosides and plasma lipoproteins. Several types of sialidases are known in mammals, of which trans-sialidase is of special interest, since it is capable of removing sialic acid from low density lipoprotein (LDL) particles and transferring it to different acceptors in blood plasma. Desialylation of LDL, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The studies indicated that there is a difference between the activity and specificity of sialidases in atherosclerotic lesions and unaffected intima [81]. Additionally, it was found that the diminished trans-sialidase activity in the blood directly correlates with the lower ability of blood serum to induce cholesterol accumulation in a culture of unaffected human aortic intimal cells [82]. Indeed, the activity of trans-sialidase in human plasma determines blood atherogenic properties.…”
Section: The Role Of Sialidases In Atherosclerosismentioning
confidence: 99%
See 3 more Smart Citations
“…The studies indicated that there is a difference between the activity and specificity of sialidases in atherosclerotic lesions and unaffected intima [81]. Additionally, it was found that the diminished trans-sialidase activity in the blood directly correlates with the lower ability of blood serum to induce cholesterol accumulation in a culture of unaffected human aortic intimal cells [82]. Indeed, the activity of trans-sialidase in human plasma determines blood atherogenic properties.…”
Section: The Role Of Sialidases In Atherosclerosismentioning
confidence: 99%
“…Furthermore, trans-sialidase can change the lipoprotein interaction with the arterial cells. It was shown that LDL desialylated by trans-sialidase causes intracellular accumulation of lipids, in association with stimulation of the proliferative activity of vascular cells and synthesis of extracellular matrix components [82]. Moreover, sialidases can change the activity of many blood cells and lipoproteins.…”
Section: The Role Of Sialidases In Atherosclerosismentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to native LDL, desialylated LDL has a higher capacity to bind to asialoglycoprotein receptor, a high capacity C-type lectin receptor, mainly expressed on hepatocytes. The interaction of desialylated LDL particles with this scavenger receptor leads to their uptake by the cell and hence to their intracellular accumulation due to reduced degradation [ 25 ]. The removal of sialic acid from LDL by neuraminidase was also found to enhance the atherogenic potential of LDL particles by increasing their capacity to accumulate intracellular cholesterol content in smooth muscle cells and macrophages [ 26 ].…”
Section: Discussionmentioning
confidence: 99%